2022
DOI: 10.1371/journal.pgen.1010156
|View full text |Cite
|
Sign up to set email alerts
|

Filling gaps in bacterial catabolic pathways with computation and high-throughput genetics

Abstract: To discover novel catabolic enzymes and transporters, we combined high-throughput genetic data from 29 bacteria with an automated tool to find gaps in their catabolic pathways. GapMind for carbon sources automatically annotates the uptake and catabolism of 62 compounds in bacterial and archaeal genomes. For the compounds that are utilized by the 29 bacteria, we systematically examined the gaps in GapMind’s predicted pathways, and we used the mutant fitness data to find additional genes that were involved in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…Initial testing indicated that the model was incapable of biomass production in EDM1 media, so we performed additional curation of model reactions and transporters ( Table S3 ). We curated the reconstruction based on genome annotations from multiple sources (Henry et al, 2010; Pascal Andreu et al, 2021; Price et al, 2022) and added transporters for strongly depleted and produced compounds that were identified with high confidence in our metabolomics data. Throughout this process, we compared model results with experimentally observed growth in chemically defined media conditions, using these results to inform the curation process and add missing reactions where supported by experimental data.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Initial testing indicated that the model was incapable of biomass production in EDM1 media, so we performed additional curation of model reactions and transporters ( Table S3 ). We curated the reconstruction based on genome annotations from multiple sources (Henry et al, 2010; Pascal Andreu et al, 2021; Price et al, 2022) and added transporters for strongly depleted and produced compounds that were identified with high confidence in our metabolomics data. Throughout this process, we compared model results with experimentally observed growth in chemically defined media conditions, using these results to inform the curation process and add missing reactions where supported by experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…In order to facilitate interpretation of FBA results and avoid excess gap-filled reactions, we used the simpler E. lenta ATCC 25559 type strain reconstruction as the basis for subsequent curation and analysis. We transferred reactions present in the DSM 2243 reconstruction into this version if they were supported by genome annotations from other sources (Prokka (Seemann, 2014), GapMind (Price et al, 2022)) and/or by experimental growth or metabolomics data. We also performed several additional custom curations.…”
Section: Star Methodsmentioning
confidence: 99%
See 3 more Smart Citations